Organizational and Economic Mechanisms of Energy Conservation and Energy Efficiency Management in Kazakhstan - Kurbanov, Farukhzhon; Sitenko, Diana; Yessengeldin, Bauyrzhan; Zhumatayeva, Bakhytzhamal; Yesbergen, Raushan (International Journal of Energy Economics and Policy, 2020)
The article considers the problem of low energy efficiency of the Kazakhstan economy and identifies opportunities for its improvement. The energy intensity indicator and the GDP structure by industry are analyzed relatively to developed countries and countries with similar climatic and territorial conditions. The legislation of recent years in the field of energy sector was studied, as well as a number of programs and strategies for energy conservation. The main problem points in the field of energy conservation and energy audit procedure are clarified by the authors. The prevalence of regulatory methods over economic ones in energy efficiency management in the country is reveled. The possibilities of using stimulating organizational and economic mechanisms for the development of energy saving as opposed to regulatory measures are considered. The use of a number of financial mechanisms to finance the transition of enterprises of Kazakhstan to the cost-effective energy conservation mode is justified. Keywords: energy efficiency, energy intensity, Kazakhstan JEL Classifications: Q4, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.8894